Small-Molecular-Weight Additives Modulate Calcification by Interacting with Prenucleation Clusters on the Molecular Level - Duchstein, Patrick; Schodder, Philipp; Leupold, Simon; Dao, Thi Quynh Nhi; Kababya, Shifi; Cicconi, Maria Rita; de Ligny, Dominique; Pipich, Vitaliy; Eike, David; Schmidt, Asher; Zahn, Dirk; Wolf, Stephan (Angewandte Chemie International Edition, 2022)
Small-molecular-weight (MW) additives can strongly impact amorphous calcium carbonate (ACC), playing an elusive role in biogenic, geologic, and industrial calcification. Here, we present molecular mechanisms by which these additives regulate stability and composition of both CaCO3 solutions and solid ACC. Potent antiscalants inhibit ACC precipitation by interacting with prenucleation clusters (PNCs); they specifically trigger and integrate into PNCs or feed PNC growth actively. Only PNC-interacting additives are traceable in ACC, considerably stabilizing it against crystallization. The selective incorporation of potent additives in PNCs is a reliable chemical label that provides conclusive chemical evidence that ACC is a molecular PNC-derived precipitate. Our results reveal additive-cluster interactions beyond established mechanistic conceptions. They reassess the role of small-MW molecules in crystallization and biomineralization while breaking grounds for new sustainable antiscalants.
CRIS-Team WoS Importer:2022-08-12